2015
DOI: 10.1016/j.celrep.2014.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Heterosynaptic Structural Plasticity on Local Dendritic Segments of Hippocampal CA1 Neurons

Abstract: SUMMARY Competition between synapses contributes to activity-dependent refinement of the nervous system during development. Does local competition between neighboring synapses drive circuit remodeling during experience-dependent plasticity in the cerebral cortex? Here, we examined the role of activity-mediated competitive interactions in regulating dendritic spine structure and function on hippocampal CA1 neurons. We found that high-frequency glutamatergic stimulation at individual spines, which leads to input… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
163
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(182 citation statements)
references
References 51 publications
12
163
3
Order By: Relevance
“…Since previous studies have shown that spontaneous activity is necessary for the spatial clustering of co-active synapses (Kleindienst et al, 2011;Takahashi et al, 2012), we expected to find either a local plasticity mechanism for potentiation of synapses that are often co-active with their neighbors or for depression of locally desynchronized synapses. In fact, evidence for cooperation and competition among neighboring synapses, at least on longer time scales (min), has been reported previously (Frey and Morris, 1997;Harvey and Svoboda, 2007;Oh et al, 2015;review: Winnubst and Lohmann, 2012). Here, we find that synaptic clustering likely arises through a ''punishing'' plasticity rule: synapses that are only rarely co-active with neighboring synapses become less reliable and their transmission frequency decreases.…”
Section: Discussionmentioning
confidence: 83%
“…Since previous studies have shown that spontaneous activity is necessary for the spatial clustering of co-active synapses (Kleindienst et al, 2011;Takahashi et al, 2012), we expected to find either a local plasticity mechanism for potentiation of synapses that are often co-active with their neighbors or for depression of locally desynchronized synapses. In fact, evidence for cooperation and competition among neighboring synapses, at least on longer time scales (min), has been reported previously (Frey and Morris, 1997;Harvey and Svoboda, 2007;Oh et al, 2015;review: Winnubst and Lohmann, 2012). Here, we find that synaptic clustering likely arises through a ''punishing'' plasticity rule: synapses that are only rarely co-active with neighboring synapses become less reliable and their transmission frequency decreases.…”
Section: Discussionmentioning
confidence: 83%
“…Second, it is compensatory because it ensures stability by effectively enforcing a constraint on the afferent synaptic weights [10,57]. Biologically, such a heterosynaptic effect could be obtained, for instance, when synapses have to compete for a shared resource [57,85] or send chemical signals to each other [86]. …”
Section: Why Do We Need Rapid Compensatory Processes To Stabilize Hebmentioning
confidence: 99%
“…This phenomenon is believed to help bind behaviorally relevant information on sub-compartments of dendrites. Another research used high-frequency glutamate uncaging to potentiate synapses of cultured hippocampal CA1 neurons (Oh et al, 2015). Interestingly, if multiple synapses on neighboring spines (≥6) are potentiated simultaneously, the inactive synapse within the cluster weakens and shrinks (see Fig.…”
Section: Clustered Structural Dynamics and Functional Plasticity Omentioning
confidence: 99%